Keragaman Budaya dan Teori Budaya Organisasi - Kasinyo Harto; lini Suryani; Tiara Nadilah; Tutut Handayani (Journal on Education, 2025)
This paper examines the important role of cultural diversity in organizational dynamics and how the application of organizational culture theory can be used to effectively manage diversity. Cultural diversity, which includes differences in values, norms, language, and social backgrounds, affects various aspects of the organization such as social interaction, communication, decision-making, and collective performance. In the context of modern organizations that are increasingly multicultural, the theory of organizational culture, especially that developed by Edgar H. Schein, provides a conceptual framework for understanding how artifacts, values adhered to, and basic assumptions shape an organization's collective identity and culture. The application of this theory allows organizations to identify inclusive core values, strengthen cultural socialization mechanisms, and manage conflicts and challenges arising from the cultural diversity of members. This strategy is essential for creating a harmonious, innovative, and adaptive work environment to external changes. With strategic and sustainable cultural management, organizations can increase productivity, competitiveness, and long-term sustainability in the face of a competitive global market. This paper asserts that managing cultural diversity is not only a normative need, but also an important strategy for organizational success. Keywords: cultural, adaptive, and organizational.